External Developmental Assets and Positive Identity Among Emerging Adults in Norway, Romania, Slovenia, and Turkey - Dost-Gözkan, Ayfer; Kozina, Ana; Stefenel, Delia; Wiium, Nora (Frontiers in Psychology, 2021)
The present study compared 2055 emerging adults’ (age range = 18 - 28) experiences of external developmental assets (support, empowerment, and boundaries and expectations) and positive identity in four countries (Norway, Romania, Slovenia, and Turkey), which have different rankings in economic, human, and youth development indices. The present study also tested a path model, which examines the links between external development assets and positive identity. Findings indicated that although there are differences in the reports of external developmental assets and positive identity, external assets and positive identity are similarly and positively linked across the four countries. The findings build on the existing literature showing that developmental assets are conducive to positive outcomes cross-nationally despite cultural differences in the experience of external assets. Policy implications of the findings were discussed from the perspective of ecological theory as well as Developmental Assets and Positive Youth Development Frameworks.